2013
DOI: 10.1097/bot.0b013e318284785a
|View full text |Cite
|
Sign up to set email alerts
|

CT Scan Assessment of the Syndesmosis

Abstract: Several studies have shown that the reduction of the syndesmosis is essential to restore normal ankle mechanics and prevent secondary degenerative changes. The evaluation criteria developed in this study can give the surgeon a guideline for evaluating syndesmosis anatomy with reliable parameters. Concerning the normal range of motion, our radiologic measurements of 100 normal ankles showed that a significant amount of variability exists in the uninjured distal tibiofibular relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
2
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(193 citation statements)
references
References 5 publications
6
175
2
10
Order By: Relevance
“…Just as with plain radiography, CT imaging has demonstrated variability in the anatomy of the syndesmosis between individuals. 64 Thus, bilateral imaging can be extremely useful. 65,66 Even after plain radiographs have demonstrated diastasis of the syndesmosis, CT scan can be a useful adjunct on the bony anatomy to guide surgical planning.…”
Section: Initial Radiographic Evaluationmentioning
confidence: 99%
“…Just as with plain radiography, CT imaging has demonstrated variability in the anatomy of the syndesmosis between individuals. 64 Thus, bilateral imaging can be extremely useful. 65,66 Even after plain radiographs have demonstrated diastasis of the syndesmosis, CT scan can be a useful adjunct on the bony anatomy to guide surgical planning.…”
Section: Initial Radiographic Evaluationmentioning
confidence: 99%
“…This was an improvement compared with a malreduction rate of 52% in a control group of twenty-five ankles that underwent postoperative CT evaluation after intraoperative fluoroscopy alone had been utilized for reduction 33 . Improved syndesmotic reduction with direct visualization of the joint has led some authors to advocate the routine use of open reduction 3,34 .…”
Section: Intraoperative Syndesmotic Reductionmentioning
confidence: 99%
“…Measurements were documented 1 cm above the centre of the tibial plafond. 8,12 Ratios were determined in order to assess the positional relationship of the tibia relative to the fibula. …”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that MRI, CT or arthroscopy should be used to ensure adequate diagnosis and treatment; [7][8][9][10]12 however, if it is possible to diagnose syndesmotic disruption with plain film radiography, significant cost and morbidity could be spared. Stress examination is another method that has been used to diagnose syndesmotic disruption; 9,[15][16][17] however, use of the mortise and AP views have continued to be the foundation for diagnosis.…”
Section: -11mentioning
confidence: 99%
See 1 more Smart Citation